Commissive Illocutionary Acts in the American Comedy Movie Entitled: Home Alone - Rahayu, Eva; Qomariana, Yana; Mas Indrawati, Ni Luh Ketut (Udayana Journal of Social Sciences and Humanities, 2024)
This study is entitled Commissive Illocutionary Acts in the American Comedy Movie Entitled: Home Alone . It focuses on a branch of speech act namely illocutionary acts, in particular to commissive and its types. The aims of this study are to identify the types of commissive illocutionary acts used by the characters in the movie and analyze the context of situation that supports the utterances which contain commissive illocutionary acts in the movie entitled Home Alone. The data of this study is taken from the American comedy movie entitled Home Alone (1990). The method used to collect the data in this study is the documentation method. The movie was watched repeatedly and the utterances was noted using note-taking technique. The descriptive-qualitative method was applied in analysing the data. In presenting the data, this study used the informal method which presented the data in the form of sentences. This study used the theory of Commissive Illocutionary Acts proposed by Searle (1969) and the theory of Context of Situation proposed by Holmes (2013); both theories were used in an attempt to answer the problems of this study. The findings of this study shows that there were forty-two utterances which are categorized under the types of commissive illocutionary acts, namely; promise, threat, refusal, intend and promise to do something, and offer to do something. Refusal type of commissive illocutionary acts is the most frequent one found in the analysis. Meanwhile, the context of situations are indeed beneficial to support the use of commissive illocutionary acts in Home Alone movie.   Keywords: commissive illocutionary acts, context of situation, home alone movie